1998
DOI: 10.1042/bj3350015
|View full text |Cite
|
Sign up to set email alerts
|

Signalling through the leukotriene B4 receptor involves both αi and α16, but not αq or α11 G-protein subunits

Abstract: COS-7 cells transfected with the leukotriene (LT) B4 receptor (BLTR) cDNA were unable to produce LTB4-induced inositol phosphates (IPs) in spite of the presence of endogenous Galphai, Galphaq and Galpha11 proteins. Co-transfection of BLTR with Galpha16, however, resulted in high levels of IP production, which were 17-, 10- and 6-fold higher than with co-transfected Galpha11, Galphaq and Galpha14, respectively. Co-transfection of BLTR with phospholipase C (PLC) beta2, on the other hand, resulted in efficient IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 39 publications
2
60
0
Order By: Relevance
“…As reported by Gaudreau et al (20), COS-7 cells expressing both BLT1 and G␣ 16 show significantly higher IP accumulation than cells expressing BLT1 alone (Fig. 3A).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…As reported by Gaudreau et al (20), COS-7 cells expressing both BLT1 and G␣ 16 show significantly higher IP accumulation than cells expressing BLT1 alone (Fig. 3A).…”
Section: Resultssupporting
confidence: 65%
“…We used HEK293 cells for GTP␥S binding assay, because HEK293 cells transiently expressing WT BLT1 showed higher LTB 4 -induced GTP␥S binding than COS-7 cells. We used COS-7 cells for the IP accumulation assay, since Gaudreu et al (20) had reported that COS-7 cells transfected with BLT1 and G␣ 16 showed LTB 4 -induced IP accumulation. CHO stable cells are commonly used for GPCR research, because they are effective in examining intracellular signaling and cellular events, such as calcium mobilization, cAMP assay, and chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies suggest that G␣ 16 coupling of chemoattractant and chemokine receptors may be important for leukocyte functions. It was shown that transmembrane signaling of the leukotriene B4 receptor is mediated by both G␣ i and G␣ 16 (43). In human T cells, alteration of the G␣ 16 expression level by cell-activating agents affects TCR-mediated functions (44).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation was terminated by replacing the medium with ice-cold 5% HClO 4 and then incubating it on ice for 2 h. The accumulated IP was purified by ion exchange chromatography (AG1-X8 resin; Bio-Rad, Richmond, CA, USA) and eluted with 0.1 M formic acid/1.0 M ammonium formate for IP 3 elution. The radioactivity was measured by scintillation counting (Gaudreau et al, 1998;Fukunaga et al, 2001).…”
Section: Inositol Phosphate (Ip) Accumulation Assaymentioning
confidence: 99%